ANALISIS MULTIPLIER EFFECT AGRIBISNIS TOMAT TERHADAP PEREKONOMIAN DI DESA TONSEWER SELATAN KECAMATAN TOMPASO BARAT - Febriani ., Kilateng; Mex L. Sondakh; Caroline B. D. Pakasi (AGRI-SOSIOEKONOMI, 2017)
This study aims to analyze using multiplier effect analysing of tomato agribusiness activity against other activities that affect the economy. Data collection consists of primary and secondary data. Primary data were obtained through a list of questions that had been prepared, while the secondary data obtained from the Head of the Agricultural Extension Agencies. The data collected by looking at the population number for eighteen tomato growers and interviews were also conducted at the Head of the Agricultural Extension Agencies (BPP) was one person. The data analysing method used is descriptive analysis and backward linkage and forward linkage analysis (multiplier effect analysis). The concept of measuring variables was used backward linkage, forward linkage, MPC1 of farmer’s income was spent in the village, and PSY, or expenditure farmer generate incomes. The results showed that the tomato agribusiness activities have backward linkage and forward linkage. The activities related to the tomato agribusiness activity has multiplier revenue of 1,090. Tomato agribusiness activity has an impact on the economy of the community.